Sindrom-Guillain Barre Pada Pasien Demam Dengue - Vivien Puspitasari (Medicinus, 2018)
Guillain-Barre syndrome is an acute poliradiculopathy that characterizes as flaccid limb weakness subsequently after an infection disease. It is scarcely found to be triggered by the dengue virus infection. Here in a case report of 48-year-old male, presented as an ascending weakness of both limbs, following 2 days fever. Anti-dengue examination was found to be positive.Keywords: Guillain-Barre Syndrome, Dengue Fever